Mitotic Poisons in Research and Medicine - Jan Škubník; Michal Jurášek; Tomáš Ruml; Silvie Rimpelová (Molecules, 2020)
Cancer is one of the greatest challenges of the modern medicine. Although much effort has been made in the development of novel cancer therapeutics, it still remains one of the most common causes of human death in the world, mainly in low and middle-income countries. According to the World Health Organization (WHO), cancer treatment services are not available in more then 70% of low-income countries (90% of high-income countries have them available), and also approximately 70% of cancer deaths are reported in low-income countries. Various approaches on how to combat cancer diseases have since been described, targeting cell division being among them. The so-called mitotic poisons are one of the cornerstones in cancer therapies. The idea that cancer cells usually divide almost uncontrolled and far more rapidly than normal cells have led us to think about such compounds that would take advantage of this difference and target the division of such cells. Many groups of such compounds with different modes of action have been reported so far. In this review article, the main approaches on how to target cancer cell mitosis are described, involving microtubule inhibition, targeting aurora and polo-like kinases and kinesins inhibition. The main representatives of all groups of compounds are discussed and attention has also been paid to the presence and future of the clinical use of these compounds as well as their novel derivatives, reviewing the finished and ongoing clinical trials.